The defence of mistake of law in international criminal law : a study on ignorance and blame - Coco, Antonio (Lawyer) (Oxford : Oxford University Press, 2022)
Ignorance and mistake of law tend to exclude responsibility in national and international criminal law. This monograph updates the existing reviews of law and practice on the topic and focuses on the appropriateness of imposing a guilty verdict on the individual defendant.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 6, 2022).
Keywords: Criminal liability (International law); Mistake (Criminal law); Law; Laws of specific jurisdictions & specific areas of law